Multi-objective Solid Transportation Problem in Uncertain Environment - Dalman, Hasan; Sivri, Mustafa (SPRINGER INTERNATIONAL PUBLISHING AG, 2017)
Although new information technologies decrease information and transaction costs, transportation problem of physical goods is still relevant. Globalization of trade increased the uncertainty that companies are facing, it also increased the importance of supply chain management in world economies drastically. Because transportation systems are crucial for operation management, the problem of finding efficient and sustainable solutions under such uncertain environments needs to be studied. Thus, this paper focuses on multi-objective solid transportation problem (STP) in uncertain environment'' and presents some approaches to find the compromised optimal solution of multi-objective STP. Then, compatible with uncertainty, fuzzy programming and some techniques of the fuzzy set theory are implemented to solve the problem by using Maple 17.02. A numerical example is executed and presented here to illustrate suggested procedures.
Keywords: Multi-objective solid transportation; Interval numbers; Goal programming; Fuzzy programming; Global criteria; OPTIMIZATION; Science & Technology - Other Topics